(untitled) (Journal of Oriental Studies, 2018)
In Kazakhstan, which actively participates in the Chinese initiative “Economic belt of the Silk Road”, China’s plans to build railroads in the south direction to the countries of Indochina are less known. At the same time, the region of East and South-East Asia is a priority for China. The region is connected with China by a common history, the roots of a common civilization. In the second half of the 20th century, the region drew the attention of the world community, demonstrating new models of economic development, it was here that the newly industrialized countries (NIS) appeared. In addition, the region is a zone of intense US attention. Here are his long-standing partners ‒ Japan, South Korea, and Australia. In connection with the strengthening of China, its transformation into the second economy of the world, the confrontation between the US and China in the region is steadily growing. Under these conditions, China’s plans to involve the Indochina countries in land and sea initiatives to revive the New Silk Road can significantly affect the alignment of forces. The methodology of the research is general scientific principles of cognition of economic and political phenomena – dialectical, concrete historical, systemic, which allow us to consider the interests of Kazakhstan and the countries of Southeast Asia along the New Silk Road, The originality / value of this study is that it considers the possible participation of the countries of the region in the Chinese initiative “The Economic Belt of the New Silk Road” and their use of the territory of Kazakhstan for transit transport to Europe.